Dehydration in the nursing home: Recognition and interventions taken by Dutch nursing staff. (30th August 2021) - Paulis, Simone J. C.; Everink, Irma H. J.; Halfens, Ruud J. G.; Lohrmann, Christa; Schols, Jos M. G. A.
Abstract: Aims: To examine which signs/symptoms registered nurses (RNs) and certified nurse assistants (CNAs) (nursing staff) in Dutch nursing homes associate with dehydration, if they observe these signs/symptoms themselves and what they do after observing them. Design: A cross‐sectional study. Methods: In February 2020, using an online questionnaire based on a diagnostic strategy to diagnose dehydration, nursing staff was asked: (1) which signs/symptoms they associate with dehydration; (2) if they observe these signs/symptoms themselves; and (3) which actions they take after observing these signs/symptoms in a resident. Descriptive statistics and Chi‐square statistics were used to describe the answers and explore significant differences between groups. Results: In total, 250 RNs and 226 CNAs participated. Among RNs, 67%–99% associated the signs/symptoms of the strategy to dehydration compared with 45%–98% of the CNAs. RNs and CNAs often indicated to observe signs/symptoms from the strategy themselves (80.1% and 92.6%), but they also often relied on information given by other care professionals and the informal caregiver. Interventions taken were mainly focused on communicating findings to colleagues. Conclusion: Many signs/symptoms from the diagnostic strategy trigger nursing staff to think of dehydration. Results also show that a variety of formal and informal caregivers are involved in dehydration care. As RNs and CNAs did often not receive dehydration training after entering workforce, this could have limited their ability to recognize signs/symptoms related to dehydration. To ensure timely recognition of dehydration, a clear description of roles and responsibilities about dehydration care in, and between, formal and informal caregivers is essential with structurally embedded dehydration training in the nursing home. Impact: Tackling dehydration in the nursing home requires interdisciplinary collaboration and communication with family members. Without clear roles and responsibilities, a risk of dehydration can be left unattended.